Arbitrary Manipulation of Light Intensity by Bilayer Aluminum Metasurfaces. Issue 13 (2nd May 2019) - Li, Zhancheng; Liu, Wenwei; Cheng, Hua; Choi, Duk‐Yong; Chen, Shuqi; Tian, Jianguo
Abstract: Realizing the arbitrary manipulation of light intensity on the microscale is a fundamental requirement for the miniaturization and integration of optical devices, which would have a substantial impact in the fields of high‐resolution imaging and information encryption. Metasurfaces, which have unprecedented capabilities for light manipulation, provide an alternative way to achieve this requirement. Here, alignment‐free bilayer metasurfaces composed of aluminum nanorods are utilized to realize full and broadband polarization‐selective transmission of optical waves in the near‐infrared band. By independently adjusting the orientation angle of each nanorod, it is demonstrated that the proposed design is an appealing alternative for realizing arbitrary intensity manipulation of linearly polarized light; further, it is experimentally validated that the proposed bilayer metasurfaces can be widely used for microscale modulation of light intensity, gray imaging with high resolution, optical polarization encoding, and anti‐counterfeiting. The proposed bilayer metasurfaces pave the way for implementing the arbitrary manipulation of light intensity on the microscale. Abstract : Bilayer metasurfaces composed of aluminum nanorods are utilized to realize arbitrary and broadband transmission intensity manipulation of linearly polarized light. With the advantages of being alignment free and having a broadband and wide‐angle optical response, the proposed metasurfaces can be widely used for microscale modulation of light intensity, gray imaging with high resolution, optical polarization encoding, and anti‐counterfeiting.